1977
DOI: 10.1111/j.1748-5827.1977.tb05915.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal obstruction due to a nodular hyperplastic tracheitis in a dog

Abstract: A case of a hyperplastic tracheitis of unknown aetiology is recorded. The physical, radiographic, bronchoscopic and histopathological findings are described and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…9 However, histologically the nodules consisted of fibrous granulation tissue admixed with few neutrophils and covered by pseudostratified epithelium. 9 Kelly 11 described a case of tracheal papillomatosis in which multiple mucosal nodules were identified, but localised to the bifurcation of the trachea and entrance of the main bronchi. Histopathology of the tracheal nodules was consistent with papillomas similar to those seen in canine oral papillomatosis of viral origin.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…9 However, histologically the nodules consisted of fibrous granulation tissue admixed with few neutrophils and covered by pseudostratified epithelium. 9 Kelly 11 described a case of tracheal papillomatosis in which multiple mucosal nodules were identified, but localised to the bifurcation of the trachea and entrance of the main bronchi. Histopathology of the tracheal nodules was consistent with papillomas similar to those seen in canine oral papillomatosis of viral origin.…”
Section: Discussionmentioning
confidence: 97%
“…1 3 6 14 15 Nodular hyperplastic tracheitis, amyloidosis, tracheal papillomatosis and tracheobronchopathia osteochondroplastica have also been rarely described as a cause of nodular tracheal lesions in dogs. [9][10][11][12] The presence of tracheal granulomas is commonly described in the veterinary literature and it is often a consequence of chronic tracheal inflammation. [14][15][16] The development of granulation tissue within the tracheal lumen has been described in up to 33 per cent of dogs with tracheal collapse following stent placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Nodular epithelial hyperplasia also has been described in association with chronic tracheitis. 16 Treatment of TO in people is not indicated unless nodules are causing airway obstruction, in which case endoscopic removal or laser therapy is often performed. Treatment of other accompanying diseases often is appropriate.…”
mentioning
confidence: 99%
“…canine mast cell tumor, T-cell lymphoma), parasitic granulomas, abscesses due to a foreign body, inflammatory mucosal polyps and trauma usually cause nodular lesions in the dog, resulting in tracheal obstruction (Beck et al 1999;Clifford & Sorenmo 2004;Sherding 2004). Hyperplastic tracheal nodules of unknown origin (De Rick et al 1977) or related to amyloidosis (Besancon et al 2004) have also been reported. The magnitude of clinical signs correlates with the severity of tracheal obstruction.…”
mentioning
confidence: 99%